2015
DOI: 10.3109/10826084.2015.1058825
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Drug Use and Health Service Access Among Street-Involved Youth in a Canadian Setting

Abstract: Background/ Objectives Addiction severity has been associated with numerous social- and health-related harms. This study sought to examine the prevalence and correlates of high intensity drug use among street-involved youth in a Canadian setting with a focus on high-risk drug use practices and health service access. Methods Data were derived from the At-Risk Youth Study (ARYS), a Vancouver-based prospective cohort of street-involved youth aged 14-26. We used generalized estimating equations (GEE) to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…However, young peoples’ description of cannabis use as a strategy for self-detoxification may also reflect their difficulty gaining access to addiction treatment (Phillips et al, 2014; Phillips et al, 2015), including medically supervised detoxification. This was also evident in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, young peoples’ description of cannabis use as a strategy for self-detoxification may also reflect their difficulty gaining access to addiction treatment (Phillips et al, 2014; Phillips et al, 2015), including medically supervised detoxification. This was also evident in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…We found that FSWs who experienced a period of homelessness, but still maintained a good financial situation, were more likely to smoke methamphetamine daily. Others have found a similar link between frequency of drug use and homelessness . The proposed mechanism behind the counterintuitive modifier of income is that higher income women may be prioritising the purchase of methamphetamine over securing housing .…”
Section: Discussionmentioning
confidence: 94%
“…Increased addiction severity may result in more frequent drug administration leading to both more opportunities to use unsterile syringes, and increased need for means to pay for drugs. Reasons young people have difficulty seeking addiction treatment are numerous, and include perceived and real discrimination from healthcare workers, fear of being reported to police or child protection authorities, and organizational barriers such as requiring a fixed address (Barker, Kerr, Nguyen, Wood, & DeBeck, 2015; Haley & Roy, 1999; Phillips et al, 2014; Phillips et al, 2015). Efforts to increase access to addiction treatment, particularly that is trauma-informed, should be a priority.…”
Section: Discussionmentioning
confidence: 99%